Taxonomic notes on Some Species of Genus Urochloa from Nepal - Neupane, Ajay; Jnawali, Bikram (Adhyayan Journal, 2022)
The purpose of this paper is to study Urochloa species and update information on the genus in light of recent changes in the taxonomy of the Poaceae family. Urochloa is popularly known as para grass. Disease-free specimens were collected and their morphological features, such as roots, stems, leaves, and floral parts, were studied. Herbarium specimens from KATH were also examined. Five species of Urochloa, namely, Urochloa subquadripara, U. distachya, U. kurzii, U. ramosa, and U. villosa, were studied. As per observation, taxonomic notes, illustrations, and keys were made.